ANALISIS IMPLEMENTASI MOTIVASI KERJA DALAM MENINGKATKAN KINERJA KARYAWAN SINOHYDRO CORPORATION LIMITED JAKARTA SELATAN - Sunaryo; Rizka Wahyuni Amelia (Journal of Research and Publication Innovation, 2025)
The purpose of this study is to know the role of motivation in improving employee performance at Sinohydro Corporation Limited South Jakarta, to know what are the indicators that support motivation in improving employee performance at Sinohydro Corporation Limited South Jakarta as an effort to improve employee performance. researchers use a qualitative approach, qualitative research aims to obtain in-depth data, a data that contains meaning. The results of this study obtained from interviews with the researchers to the objects indicate that the relationship between employees and superiors is very influential, because by having a good boss, friendly and wanting to mingle with his employees and provide input to all to work in a relaxed but sure manner, both managers and employees. others, so that employees can work well and comfortably. Skills must exist every work. If the motivation to work is high but the skills are still lacking, it will not affect work. So it's good that Skill is accompanied by motivation so the work will be good and smooth. Internal motivational factors that drive employee performance at Sinohydro Corporation Limited South Jakarta are working diligently in order to achieve the desire to be able to survive, own, gain recognition, gain career paths in accordance with the theory of work motivation according to Anwar Prabu Mangkunegara. External motivational factors that drive employee performance at Sinohydro Corporation Limited South Jakarta are a strategic location and a clean workplace, appropriate salaries and bonuses, managers who guide and provide direction, and job security in accordance with the theory of work motivation according to Mangkunegara.